Economic mobility likely to increase significantly after relaxation - but also number of COVID-19 cases - Oliver Holtemöller; Malte Rieth (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2021)
In Germany, measures to contain the coronavirus were relaxed in some areas at the beginning of March; in many places, for example, the restrictions on private and public gatherings were eased, and retail stores are increasingly able to receive customers again. The aim of these decisions is to allow for more economic mobility and personal contact between people. However, the frequency of contact is a major factor influencing the rate at which the coronavirus spreads, especially since the relaxations have so far not been accompanied by a systematic testing strategy; and vaccination progress has so far also fallen short of expectations. Estimates based on a model of the relationship between containment measures (Oxford COVID-19 Government Response Tracker, Stringency Index), economic mobility (Google Mobility Data), new corona infections, and deaths with data from 44 countries suggest that the recent relaxations increase economic mobility by ten percentage points and the number of new infections and deaths in Germany by 25%. Because both continued lockdown and relaxations have significant negative consequences, it is even more important to enable further relaxations through better testing and quarantine strategies and by increasing the pace of vaccination without putting people's health at risk. – – In Deutschland wurden Anfang März in einigen Bereichen Maßnahmen zur Eindämmung des Coronavirus gelockert; so wurde die Anzahl der Personen aus verschiedenen Haushalten, die sich treffen dürfen, vielerorts erhöht und Einzelhandelsgeschäfte können vermehrt wieder Kunden empfangen. Auf diese Weise kommt es zu einem gewollten Wiederanstieg der wirtschaftlichen Mobilität und der persönlichen Kontakte zwischen Menschen. Die Kontakthäufigkeit ist allerdings auch ein wesentlicher Einflussfaktor für die Ausbreitungsgeschwindigkeit des Coronavirus, zumal die Lockerungen bislang nicht mit einer systematischen Teststrategie einhergehen; und auch der Impffortschritt bleibt hinter den Erwartungen zurück. Schätzungen auf Basis eines Modells für den Zusammenhang zwischen Eindämmungsmaßnahmen (Oxford COVID-19 Government Response Tracker, Stringency Index), wirtschaftlicher Mobilität (Google Mobility Data), Corona-Neuinfektionen und Todesfällen mit Daten aus 44 Ländern deuten darauf hin, dass die jüngsten Lockerungen die wirtschaftliche Mobilität um mehr als zehn Prozentpunkte ansteigen lassen und die Zahl der Neuinfektionen und der Todesfälle in Deutschland um 25% erhöhen. Da sowohl ein fortgesetzter Lockdown als auch Lockerungen erhebliche negative Konsequenzen mit sich bringen, ist es umso wichtiger, durch eine bessere Test- und Quarantänestrategie und durch eine höhere Geschwindigkeit beim Impfen weitere Lockerungen zu ermöglichen, ohne damit die Gesundheit der Menschen zu gefährden.
Keywords: E32; H8; I1; 330; containment policy; coronavirus; lockdown; mobility